Some chemical properties of mineral soil under peat layer at Sriwijaya Botanical Garden - Poppy Khairunnisa; Bakri Bakri (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Natural peat forms from partially decomposed plant remains, at least 50 cm thick, accumulating in swamps over alluvial subsoil. The research aimed to identify peat maturity, peat depth and color of mineral soil. Additionally, to identify some soil chemical properties such as soil pH, N-total, C-organic and P-available under the peat layer in Siwijaya Botanical Garden. This study used a detailed survey method at a scale of 1:8,000 on peatland areas in Sriwijaya Botanical Garden covering 77 ha. Sampling was conducted using the systematic sampling method. The analysis of soil chemical properties was conducted in the laboratory. The study results showed that the thickness of the peat at the study location was dominantly very deep with a peat depth of >300 cm, the color of the mineral soil in the peat layer was predominantly gray and very dark gray, the pH value of the soil was very acidic with a value of <4.5, the C-Organic value was categorized as average to very high, the N-Total value was categorized as very low to average and the P-Available value was categorized as very low to low. Peat depths of more than 300 cm should be planted with conservation crops and further research needs to be done on the relationship between the chemical properties of the mineral soil under peat layers and the chemical properties of the peat soil.